The Urinary Tract A Comprehensive Guide to Patient Diagnosis and Management - Hansel, Donna E.; McKenney, Jesse K.; Stephenson, Andrew J.; Chang, Sam S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Providing a true integration of pathology with clinical management, this volume presents a practical, comprehensive text on benign and malignant disease of the adult bladder. Integrating pathology, surgical management, oncology and molecular study in a site-specific manner to include the urethra, urinary bladder, ureter and renal pelvis, The Urinary Tract: A Comprehensive Guide to Patient Diagnosis and Management is the first text in adult bladder disease to closely interweave multiple clinical disciplines into each chapter. For the majority of chapters, a pathologist and urologist or urologic oncologist are paired to provide the greatest integration of information for each disease process.
Part I: The Urinary Tract -- Chapter 1. Anatomy, Embryology, and Histology -- Part II: Non-neoplastic Diseases of the Bladder -- Chapter 2.  Benign Polypoid and Papillary Lesions -- Chapter 3.  Diverticular Disease -- Chapter 4.  Infection and Inflammatory Disorders -- Part III: Bladder Neoplasia -- Chapter 5.  Bladder Cancer Overview and Staging -- Chapter 6.  Non-muscle-invasive Low- and High-Grade Neoplasia -- Chapter 7. Muscle-invasive Urothelial Carcinoma: Conventional and Variant Subtypes -- Chapter 8.  Micropapillary Carcinoma -- Chapter 9.  Small Cell Urothelial Carcinoma -- Chapter 10.  Squamous Cell Carcinoma -- Chapter 11.  Adenocarcinoma of the Urinary Bladder -- Chapter 12.  Mesenchymal Lesions of the Urinary Bladder -- Part IV: Urethral Disease -- Chapter 13. Non-Neoplastic and Neoplastic Urethral Disease -- Part V: Upper Tract Disease -- Chapter 14.  Non-neoplastic and Neoplastic Ureteral and Renal Pelvis Disease -- Part VI: Chemotherapy and Long-Term Patient Follow-Up -- Chapter 15. Urothelial Carcinoma: Role of Perioperative Systemic Chemotherapy -- Chapter 16. Urine Cytology -- Chapter 17. Pathology-Endoscopy Correlations of Bladder, Urachal, and Urethral Lesions -- Chapter 18.  Molecular Pathogenesis of Bladder Cancer.
Keywords: Pathology; Urology; Oncology .; Pathology; Urology; Oncology